Local Knowledge and Longevity: An Ethnobotanical Analysis of the Miduana Traditional Village Community, Cianjur - Usman Supendi; Teddiansyah Nata Negara; Dedy Frianto; Muhammad Utari; Hafiz Fadhlan (Journal of General Education and Humanities, 2026)
This study addresses the problem of how indigenous communities maintain cultural continuity, ecological balance, and health resilience amid the pressures of modernization. Focusing on Kampung Adat Miduana in Cianjur, West Java, this research aims to analyze the relationship among local knowledge, ritual practices, ecological wisdom, and longevity within the community. This study employs a qualitative ethnographic method, collecting data through in-depth interviews, participant observation, and documentation with traditional leaders, ritual practitioners, elders, and community members. The results show that the longevity of the Miduana community is closely related to a natural lifestyle, including a plant-based diet, consumption of untreated spring water, regular physical activity through farming and walking in mountainous areas, and a balanced psychological-spiritual life rooted in Islamic values and local traditions. The community also utilizes approximately 120 medicinal plants and maintains ecological practices that support both health and environmental sustainability. In addition, agricultural rituals and communal traditions function as mechanisms of social cohesion, cultural transmission, and environmental awareness. This study concludes that Kampung Adat Miduana represents a sustainable indigenous model of living that integrates health, spirituality, local knowledge, and environmental harmony, although modernization remains a challenge to cultural preservation.